Komunikasi Konsep Bekerja di Era Millenial: Analisis Kritis Perubahan Konsep Lapangan Pekerjaan - Hidayatul Rachmad, Teguh (Unitri Press, 2020)
The symbol of change in everything in the human sphere is marked by the disruptive era, which is an era in which activity, interaction and communication between humans changes very rapidly, especially in the field of work and the needs of human life. Work is no longer required to leave the house and must come on time at the office. The research method used is qualitative research with a critical approach. Dismantling the domination of an emancipatory spirit is one of the goals of the critical approach. The choice of social media as a place for creativity is effective because there is no filter of information in the media. everyone has the right and obligation to photos, videos and various kinds of individual works to be published on social media. Many creative content has finally appeared on social media with cultural, ethnic and religious backgrounds from different accounts. Influencers are a job that is in demand by people in the current millennial era. The era of postmodernism has changed the concept of working from the public to the private sphere. Work does not have to go to the office and meet and collaborate with many people. Work in the postmodern era can be done anywhere, for example at home, on the beach, in the mountains, in the village, in the city and does not have to meet many people.